LIQUIDUS AND PHASE EQUILIBRIA IN CaO-Al2O3-FeOx-SiO2 SYSTEM UNDER INTERMEDIATE OXYGEN PARTIAL PRESSURE - wang, nan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Liquidus and phase equilibria in CaO-Al2O3-FeOx and CaO-Al2O3-FeOx-SiO2 systems under intermediate oxygen partial pressures of 10.13Pa and 1.01´10-1Pa have been experimentally investigated, by means of high temperature equilibration, quenching technique, Scanning Electronic Microscope with Energy Dispersive Spectrometer (SEM-EDS), and X-ray Diffraction (XRD). For CaO-Al2O3-FeOx system, both two-phase coexistence and three-phase coexistence, including liquid, CaAl2O4, CaAl4O7 and spinel, are observed in high Al2O3 zone at either 10.13Pa or 1.01´10-1Pa oxygen partial pressure, but the equilibrated phases at 1450℃ are a little different from those at 1550℃. With addition of 10mass% SiO2, melilite phase was found around the primary phase field of CaAl4O7 in CaO-Al2O3-FeOx-SiO2 system. The liquidus data around the boundaries of CaAl2O4 and CaAl4O7 primary phase fields in CaO-Al2O3-FeOx system are obtained under the two intermediate oxygen partial pressures, and the effect of oxygen partial pressure on the liquidus has been discussed.